2007
DOI: 10.1097/nen.0b013e3181257176
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Attenuates Neuronal Death and Promotes Functional Recovery After Spinal Cord Injury in Mice

Abstract: Granulocyte colony-stimulating factor (G-CSF) is a protein that stimulates differentiation, proliferation, and survival of granulocytic lineage cells. Recently, a neuroprotective effect of G-CSF was reported in a model of cerebral infarction. The aim of the present study was to elucidate the potential therapeutic effect of G-CSF for spinal cord injury (SCI) in mice. We found that G-CSF is neuroprotective against glutamate-induced cell death of cerebellar granule neurons in vitro. Moreover, we used a mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 26 publications
3
79
0
1
Order By: Relevance
“…For example, G-CSF promoted neuronal survival, oligodendrocyte protection, and functional recovery in animal models of spinal cord injury (SCI) (47,76). In phase I/IIa clinical trials, the safety and feasibility of G-CSF as a neuroprotective therapy in patients with acute SCI were described, indicating the possibility for G-CSF to improve neurological and functional outcomes in patients with acute SCI (110).…”
Section: Therapeutic Uses Of G-csfmentioning
confidence: 99%
“…For example, G-CSF promoted neuronal survival, oligodendrocyte protection, and functional recovery in animal models of spinal cord injury (SCI) (47,76). In phase I/IIa clinical trials, the safety and feasibility of G-CSF as a neuroprotective therapy in patients with acute SCI were described, indicating the possibility for G-CSF to improve neurological and functional outcomes in patients with acute SCI (110).…”
Section: Therapeutic Uses Of G-csfmentioning
confidence: 99%
“…Cell counting included the area from either 300 to 800 ÎŒm rostral or 300 to 800 ÎŒm caudal to the lesion epicenter as previously described. 19 The examiners were blinded as to the treatment condition of the mice.…”
Section: Double Immunofluorescence Stainingmentioning
confidence: 99%
“…G-CSFR is present within the CNS 17 and increasing evidence has revealed that G-CSF may inhibit neuronal apoptosis associated with neural injury/disease and, in this way, promote neuroprotective effects. [18][19][20] In particular, G-CSF has been shown to exert beneficial effects via an anti-autophagic mechanism in cardiomyopathic hamster models. 21 Based upon these findings, the potential for G-CSF to function as a neuroprotectant in acute SCI attracted our attention.…”
mentioning
confidence: 99%
“…Several recent reports have indicated that G-CSF also has nonhematopoietic functions and can potentially be used for the treatment of neuronal injury, including stroke and neurodegenerative diseases [4,7,9,18,20]. We previously demonstrated that G-CSF promoted the restoration of damaged spinal cord tissue and the recovery of neural function in experimental spinal cord injury in both mice and rats [8,14]. In addition, we showed that G-CSF promoted the migration of bone marrow-derived cells into the damaged spinal cord, suppressed apoptosis of neuronal cells and oligodendrocytes, protected myelin, decreased inflammation, and promoted angiogenesis [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that G-CSF promoted the restoration of damaged spinal cord tissue and the recovery of neural function in experimental spinal cord injury in both mice and rats [8,14]. In addition, we showed that G-CSF promoted the migration of bone marrow-derived cells into the damaged spinal cord, suppressed apoptosis of neuronal cells and oligodendrocytes, protected myelin, decreased inflammation, and promoted angiogenesis [8,14]. Based on these results, we have suggested that G-CSF is a candidate for neuroprotective therapy for worsening symptoms of compression myelopathy.…”
Section: Introductionmentioning
confidence: 99%